Upaya Mempertahankan Ekowisata Mangrove Demi Keberlangsungan Lingkungan - Virgo Nugraha; Selamet Siswanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study explores the efforts made to maintain mangrove ecotourism in order to maintain environmental sustainability. The research focus is on conservation strategies, community participation, and ecotourism management. Data was collected through field observations and interviews with relevant stakeholders. The results show the importance of collaboration between government, communities and non-government organizations in protecting mangrove ecosystems. Increasing public awareness and implementing sustainable practices are key in maintaining mangrove ecotourism and ensuring sustainable environmental sustainability.